Avaliação da extensão e severidade dos defeitos de desenvolvimento do esmalte dos incisivos maxilares em indivíduos nascidos com fissura labial e/ou palatina - Lavôr, Juliane Rolim de (2020)
Cleft lip with or without cleft palate (CLP) is considered the most frequent congenital malformations of the head and neck, with cleft individuals exhibiting more chances of presenting abnormalities such as developmental defects of enamel (DDE). Matrix metallopeptidase 2 (MMP2) is a membrane-bound protein with collagen-degrading ability and have important roles in tooth formation and mineralization. This study aimed to evaluate the frequency, type of enamel defect, location, severity and extent of DDE found in the permanent maxillary incisors for groups of individuals born with CLP, as well as understanding their relationship with the cleft side. Besides, this study addresses the hypothesis that DDE can be influenced by variation in the MMP2 genes (rs9923304). Saliva samples, clinical history and intraoral photographs were obtained from 233 patients (age percentiles 9, 12, 15) under treatment at the Cleft Lip and Palate Service of the University Hospital Lauro Wanderley at the Federal University of Paraíba. Digital images were examined by the same evaluator using the Modified DDE Index (k intraexaminer = 0.88), and then loaded into the Image Tool software, where two measurements in the maxillary incisors were made: the proportion of the total area of the buccal surface (SA) and the area of enamel defect (DA), obtaining the percentage of the surface area affected (%SAD) (ICC=0.99). Genomic DNA was extracted from saliva samples from 124 participants. Genotyping was carried out using TaqMan chemistry for one marker in MMP2 (rs9923304). Statistical analyses were performed by The Jamovi Project software. The Shapiro-Wilk test was applied, followed by the Student’s t-test and the Mann-Whitney test. Chi-square and Fisher’s exact tests, and odds ratio (OR) with 95% confidence interval (CI) calculations were used to determine Hardy-Weinberg equilibrium and evaluative associations between DDE and clefts (α = 0.05). No significant differences in the prevalence and extent of DDE were found between male and female individuals born with CLP (p=0.06). The frequency of individuals presenting incisors with DDE, in relation to the cleft and non-cleft side, was statistically different (p <0.001; OR = 7.15, CI: 4.674 - 10.942). However, the averages of %SAD were similar (p = 0.18). The highest means of the %SAD were found in individuals with bilateral cleft lip with or without cleft palate (BCLP) when compared to individuals with unilateral cleft lip with or without cleft palate (UCLP), for the incisors inside (IA) and outside 11 the cleft area (OA) (p <0.001). Regardless of the cleft side, BCLP was 7.85 times more likely to have more than one third of the tooth surface affected, showing more frequently DDE in the three thirds (OA: p <0.001) (IA: p = 0.03), as well as a higher frequency of more than one type of DDE (OA: p <0.001) (IA: p = 0.008), whereas in UCLP, DDE were isolated and restricted to only one third, more frequently, the incisal third (OA: p = 0.009) (IA: p = 0.001), with greater frequency of milder defects, such as demarcated (p = 0.02) and diffuse (p = 0.008) opacities. A higher frequency of the T allele, less common, was observed in the group of CLP individuals who had all the affected incisors or at least two incisors with %SAD greater than 20% (p = 0.02). Our results suggest that MMP2 may have a role in the cases that presented DDE and genotyping rs9923304 could serve as the basis for a genomic approach to define risks for individuals born with CLP. Frequency and severity of DDE is strongly related to the CLP phenotype, since the highest values were found for BCLP. However, the extent of the DDE is independent of its relationship with the side of the cleft.